2014
DOI: 10.3390/rel5030814
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Relationships in Muslim Families: A Qualitative Examination of Devout Married Muslim Couples

Abstract: Abstract:Since 11 September 2001, Islam has been the center of many debates, discussions, parodies and publications. Many Muslims feel that their religion has been portrayed unfairly in Western media. The topics that seem to generate the most criticism relate to gender roles and the treatment of women, both inside the home and in society. The purpose of this paper is to examine the perceived role of Islam on marital and familial relationships from an insider's perspective and to present participants' reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…A review including 94 meta-analysis studies referred to an average to strong relationship between religion and commitment and marital satisfaction. The results of the studies carried out on Muslim, Christian, and Jewish Americans indicated that religion affected the marriage stability through channels like anti-divorce beliefs and sharing religious beliefs among public (61). In different studies of appropriate criteria in spouse selection, adherence to religious beliefs and principles was among the first priorities (12, 60, 62).…”
Section: Resultsmentioning
confidence: 99%
“…A review including 94 meta-analysis studies referred to an average to strong relationship between religion and commitment and marital satisfaction. The results of the studies carried out on Muslim, Christian, and Jewish Americans indicated that religion affected the marriage stability through channels like anti-divorce beliefs and sharing religious beliefs among public (61). In different studies of appropriate criteria in spouse selection, adherence to religious beliefs and principles was among the first priorities (12, 60, 62).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since the New York City terrorist attacks on September 11, 2001, Islam has been central in many debates, discussions, and publications (Alghafli et al, 2014). Discussion on Islam frequently concerns familial issues, perceived by the Western media mostly in a negative light.…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, social research on religion in the United States has been criticized for repeatedly employing predominantly White Christian samples (Alghafli, Hatch, & Marks, ; Mahoney, ; Marks & Dollahite, ). We strived to address and overcome these limitations with intentional sampling (e.g., Daly, ).…”
Section: Methodsmentioning
confidence: 99%
“…As previously noted, social research on religion in the United States has been criticized for repeatedly employing predominantly White Christian samples (Alghafli, Hatch, & Marks, 2014;Mahoney, 2010;. We strived to address and overcome these limitations with intentional sampling (e.g., Daly, 2007 Ethnic and racial minority families were oversampled such that they comprised 51.5% of the total sample (n = 102 families).…”
Section: Sampling and Participantsmentioning
confidence: 99%